Contratexto asks Miquel de Moragas - Moragas, Miquel de (1986)
The electoral triumph of the APRA party in the recent presidential elections in Peru has provoked multiple interpretations. After 55 years of struggle for power (which remained under the exclusive and patriarchal leadership of the president and founder of APRA, Víctor Raúl Haya de la Torre), the APRA party came to power in 1985, this time under the leadership of a new leader, Alan García Pérez.